Learning From Mistakes: The Role of Phages in Pandemics - Alsaadi, Ahlam; Beamud, Beatriz; Easwaran, Maheswaran; Abdelrahman, Fatma; El-Shibiny, Ayman; Alghoribi, Majed F.; Domingo-Calap, Pilar (Frontiers in Microbiology, 2021)
The misuse of antibiotics is leading to the emergence of multidrug-resistant (MDR) bacteria, and in the absence of available treatments, this has become a major global threat. In the middle of the recent coronavirus SARS-CoV-2 pandemic, which has challenged the whole world, the emergence of MDR bacteria is increasing due to prophylactic administration of antibiotics to intensive care unit patients to prevent secondary bacterial infections. This is just an example underscoring the need to seek alternative treatments against MDR bacteria. To this end, phage therapy has been proposed as a promising tool. However, further research in the field is mandatory to assure safety protocols and to develop appropriate regulations for its use in clinics. This requires investing more in such non-conventional or alternative therapeutic approaches, to develop new treatment regimens capable of reducing the emergence of MDR and preventing future global public health concerns that could lead to incalculable human and economic losses.